Application of the Kaizen Method to improve the quality and efficiency of Company Production - Suwanda, Suwanda (Journal of Economics and Business (JECOMBI), 2023)
The Kaizen method, which originates from Japan, is known as a continuous approach to process improvement that emphasizes employee participation, reduced waste, and increased efficiency. This research aims to investigate the impact of applying the Kaizen Method in improving company quality and efficiency. This research uses a qualitative approach with descriptive methods. The results of this research reveal that applying the Kaizen method in a company can significantly increase production efficiency and product quality in a sustainable manner. By focusing on waste reduction, operational standardization, employee training, and the use of quality tools such as Pareto charts, root cause analysis, and statistical process control (SPC), companies are succeeding in identifying, analyzing, and addressing quality problems more effectively. Involving employees from various levels, including the design team, in the Kaizen process also has a positive impact on innovation in product design.